2017
DOI: 10.3390/beverages3030037
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Milk Sphingomyelin Reduces Systemic Inflammation in Diet-Induced Obese Mice and Inhibits LPS Activity in Macrophages

Abstract: High-fat diets (HFD) increase lipopolysaccharide (LPS) activity in the blood and may contribute to systemic inflammation with obesity. We hypothesized that dietary milk sphingomyelin (SM), which reduces lipid absorption and colitis in mice, would reduce inflammation and be mediated through effects on gut health and LPS activity. C57BL/6J mice were fed high-fat, high-cholesterol diets (HFD, n = 14) or the same diets with milk SM (HFD-MSM, 0.1% by weight, n = 14) for 10 weeks. HFD-MSM significantly reduced serum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
37
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 64 publications
1
37
0
Order By: Relevance
“…While health effects of PLs from eggs [7] and SLs [8] have been reviewed previously, the health effects of consuming milk polar lipids have not been reviewed extensively. Since the SLs found within MFGM are known to impact various aspects of lipid metabolism [9,10], gut microbiota [10], and inflammation [9,11], milk polar lipids may be considered as food matrix factors that may confer health benefits and/or impact effects of other dietary lipids, with implications for full-fat vs. lower-fat dairy varieties. This review summarizes the recent basic science and clinical research examining food sources and health effects of milk polar lipids, as well as to identify gaps in the scientific literature related to milk polar lipids research.…”
Section: Introductionmentioning
confidence: 99%
“…While health effects of PLs from eggs [7] and SLs [8] have been reviewed previously, the health effects of consuming milk polar lipids have not been reviewed extensively. Since the SLs found within MFGM are known to impact various aspects of lipid metabolism [9,10], gut microbiota [10], and inflammation [9,11], milk polar lipids may be considered as food matrix factors that may confer health benefits and/or impact effects of other dietary lipids, with implications for full-fat vs. lower-fat dairy varieties. This review summarizes the recent basic science and clinical research examining food sources and health effects of milk polar lipids, as well as to identify gaps in the scientific literature related to milk polar lipids research.…”
Section: Introductionmentioning
confidence: 99%
“…Both high‐fat fed and ob/ob mice have been associated with a metabolic endotoxemia, dependent on the translocation of LPS notably due to intestinal permeability, that can induce inflammation in target organs, namely adipose tissue and liver . Previous studies in mice fed semi‐synthetic HF diets (based on starch and casein, 40–60%kJ as fat) reported that addition of milk‐SM or MPL decreased HF‐induced inflammation, notably in EAT . Here, the chow‐based HF diet treatment itself did not induce inflammation, probably again as it was more balanced and lipids were not composed of palm oil only.…”
Section: Discussionmentioning
confidence: 76%
“…After 10 weeks of a synthetic HF diet supplemented with 0.1% of milk‐SM (60% kcal from fat, 0.15% cholesterol), Norris et al. observed no differences of body weight gain in mice; while another synthetic diet for only 4 weeks (45% kcal from fat) resulted in lower body weight gain when including SM . We previously observed no significant difference in body weight gain and adiposity when 1.2% MPL was incorporated in a palm‐oil‐based synthetic HF diet after 8 weeks with an isolipidic design .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, Gambelli [8] provides an updated picture of methodologies for the assessment of lactose. Some studies on the potential benefits of some milk components [9,10], as well as a consideration from a nutritional point of view of organic vs. conventional milk with regard to fat-soluble vitamins and iodine content [11], are also discussed.…”
Section: Introductionmentioning
confidence: 99%